2011
DOI: 10.1111/j.2041-1014.2011.00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and adherence of Porphyromonas gingivalis FimA genotypes

Abstract: SUMMARY Porphyromonas gingivalis is a primary pathogen involved in the initiation and progression of adult chronic periodontitis. Its colonization on oral surfaces is a necessary first step leading to infection. FimA, a subunit protein of major (long) fimbriae, is a well-known virulence factor. Based on its nucleotide sequence, FimA is classified into several genotypes. We compared here the transcriptional levels of the fimA gene in several P. gingivalis strains using real-time polymerase chain reaction analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 23 publications
(47 reference statements)
3
25
0
1
Order By: Relevance
“…This ability to permanently colonize distinct niches implies that these bacteria have sophisticated mechanisms to adapt to the local environment. In vitro and animal model studies confirm the clinical observations: comparison of distinct P. gingivalis strains demonstrates extensive differences in behavior and pathogenic potential [28,30,31,3952]. …”
Section: P Gingivalis Genetic Diversity and Virulencesupporting
confidence: 56%
See 2 more Smart Citations
“…This ability to permanently colonize distinct niches implies that these bacteria have sophisticated mechanisms to adapt to the local environment. In vitro and animal model studies confirm the clinical observations: comparison of distinct P. gingivalis strains demonstrates extensive differences in behavior and pathogenic potential [28,30,31,3952]. …”
Section: P Gingivalis Genetic Diversity and Virulencesupporting
confidence: 56%
“…The genetic variability of fimA probably has a significant influence on host–pathogen interactions, as the fimbriae mediate several key aspects of virulence, including manipulation of host cell responses to bacteria. In studies of P. gingivalis isolates from healthy and diseased individuals, fimA type Ib, II and IV are more commonly associated with periodontal disease, whereas types I and III are found primarily in isolates from healthy individuals [45,46,52,54]. The human studies have been confirmed by animal studies, which found that strains containing fimA type II and IV are more cytotoxic and invasive, while strains with fimA type I and III are less inflammatory and more likely to form localized selflimiting infections [55].…”
Section: P Gingivalis Genetic Diversity and Virulencementioning
confidence: 99%
See 1 more Smart Citation
“…Transmission electron microscopy of P. gingivalis was conducted as previously described (38). P. gingivalis strains ATCC 33277 and 1932E were grown anaerobically for 16 h in TSB.…”
Section: Bioinformaticsmentioning
confidence: 99%
“…Type II and IV fimA have significantly greater adhesive and invasive capabilities and are associated with more cytotoxic strains compared to other fimA type clones [15]. While type Ib, II and IV are most frequently associated with periodontitis [1418], type I and III are less inflammatory and are associated with strains more likely to form localized self-limiting infections [19]. It has been suggested that the fimA type II allele confers a selective advantage in the advanced disease process thus ensuring its distribution throughout the P. gingivalis population [20].…”
Section: Introductionmentioning
confidence: 99%